Analysis Of The Use Of Smartphones In Supporting Work - Arif, Wahyu Muhammad Zul (International Journal of Business and Information Technology, 2024)
This research aims to examine how much impact the use of smartphones has in supporting work where this is based on the rise of people now using smartphones in everyday life, especially in terms of work. This research uses quantitative with survey techniques. The sample from this study was food vendors, students, and teachers as many as 6 people using questions and reports on smartphone use in terms of work. As we know at this time smartpone has become a must for everyone because smartphones are easy to carry, use, and very important roles such as can be used to see certain tutorials, schoolwork, meetings, and when online classes teach during the corona virus pandemic